Post‐capture survival of whale sharks encircled in tuna purse‐seine nets: tagging and safe release methods. Issue 4 (10th May 2016) - Escalle, Lauriane; Murua, Hilario; Amande, Justin Monin; Arregui, Igor; Chavance, Pierre; Delgado de Molina, Alicia; Gaertner, Daniel; Fraile, Igaratza; Filmalter, John David; Santiago, Josu; Forget, Fabien; Arrizabalaga, Haritz; et al.
Abstract: 1. Whale shark, the world's largest fish, is believed to be particularly vulnerable owing to its biological characteristics (slow growth, late maturation, great longevity) and is listed as Vulnerable by IUCN and included in Appendix II of CITES. 2. Whale sharks are occasionally encircled in tropical tuna purse‐seine nets, throughout this global fishery. Although apparent immediate survival rates following encirclement and release have recently been assessed through scientific onboard observer programmes, a more rigorous methodology is still required for studying post‐released survival. 3. This work provides a method for applying pop‐up satellite tags and reports an enhanced release procedure for whale sharks. The first assessment of survival after release from purse‐seine nets involved six whale sharks tagged between May and September 2014 in the eastern tropical Atlantic Ocean. Five tags transmitted data: three popped up as programmed (after 30 days), while two surfaced prematurely (one after 21 and the other after 71 days (programmed to pop off after 30 and 90 days, respectively)) but showed no sign of unusual behaviour. 4. Overall, whale sharks survived at least 21 days (one at least 71 days) after release from purse‐seine nets. These observations based on five large individuals (total length > 8 m), suggest that whale sharks have a good chance of survival when released with the proposed method. 5. Additional tagging in this and other oceans, especially of juveniles which may be more sensitive to encirclement and release operations, is essential to further assess whale shark post‐release survival rates in tuna purse‐seine fisheries. Copyright © 2016 John Wiley & Sons, Ltd.